Strategi Guru Menerapkan Metode Yanbu’a dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Siswa SMP IT Ar-Rudho - Muhamad Nur Rizky; Muhammad Taswirul Afkar; Muhammad Rizki Fadhilah; Saiful Bahri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Qur’anic reading and writing instruction is a fundamental competency that must be mastered by students in integrated Islamic schools. One of the widely implemented approaches is the Yanbu’a Method however, its effectiveness is strongly influenced by teachers’ pedagogical strategies in its implementation. This study aims to examine in depth the pedagogical strategies employed by teachers in applying the Yanbu’a Method in Qur’anic instruction at SMP IT Ar-Rudho, as well as to identify the supporting and inhibiting factors in its implementation. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving Qur’anic teachers, the deputy coordinator of Qur’anic learning, Qur’anic examiners, and the school principal. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Yanbu’a Method at SMP IT Ar-Rudho is carried out systematically and progressively through the mapping of students’ initial abilities, ability-based grouping, guided individual instruction, habituation and repetition of recitation, and tiered evaluation based on the principle of mastery learning. The successful implementation of the method is supported by certified teachers’ competencies, the availability of adequate learning facilities, and well-organized administrative and documentation systems. The main challenges include significant differences in students’ initial abilities, limited practice time outside school, and dense academic activities. This study emphasizes that the effectiveness of the Yanbu’a Method is not solely determined by its instructional design but is highly dependent on teachers’ pedagogical strategies in managing Qur’anic learning in an adaptive and mastery-oriented manner.